2009
DOI: 10.1016/j.fusengdes.2008.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Real-time fast ferrite ICRF tuning system on the Alcator C-Mod tokamak

Abstract: A real-time ion cyclotron range of frequencies (ICRF) antenna matching system has been successfully implemented on Alcator C-Mod. This system is a triple-stub tuning system working at 80 MHz, where one stub acts as a pre-matching stub and the other two stubs use fast ferrite tuners (FFT) to accomplish fast tuning. It utilizes a digital controller for feedback control (200 μs per iteration) using real-time antenna loading measurements as inputs and the coil currents to the FFT as outputs. The system has achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…There are generally two kinds of power loss mechanisms, dubbed as dynamic loss, which can happen at any RF power level, and nonlinear loss, which only happens at very high RF power intensity. [19] In the previous study [4], we found the evidence of non-linear power loss in the ferrite tuners during high power operation during the first implementation of the tuners without Stub-3, where the circulating RF power inside the tuners was very high. After several iterations of optimization, especially with the careful design and installation of Stub-3, the circulating power in the ferrite tuners at the same net power to the antennas has been significantly lowered.…”
Section: Figure 6 Time Traces During An Edge Localized Mode (Elm) (Amentioning
confidence: 76%
See 2 more Smart Citations
“…There are generally two kinds of power loss mechanisms, dubbed as dynamic loss, which can happen at any RF power level, and nonlinear loss, which only happens at very high RF power intensity. [19] In the previous study [4], we found the evidence of non-linear power loss in the ferrite tuners during high power operation during the first implementation of the tuners without Stub-3, where the circulating RF power inside the tuners was very high. After several iterations of optimization, especially with the careful design and installation of Stub-3, the circulating power in the ferrite tuners at the same net power to the antennas has been significantly lowered.…”
Section: Figure 6 Time Traces During An Edge Localized Mode (Elm) (Amentioning
confidence: 76%
“…As a result, if plasma loading changes rapidly or varies in a large range, the transmitter would be mismatched. Many groups have studied and implemented matching systems that can be used in real-time, including frequency modulation on JET [1], dielectric liquid stubs on EAST [2] and LHD [3], ferrite tuners on Alcator C-Mod [4], EAST [5] and KSTAR [6]. In this paper, we report the recent progress on the implementation and performance of real time fast matching system using ferrite tuners on the Alcator C-Mod tokamak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] The coil currents of the tuners, and thus the electrical length of the tuners, are controlled by a Linux-server based real-time controller. During a plasma discharge, the controller reads the RF power information from the three directional couplers (DC1, DC2 and DC3) as shown in Fig.…”
Section: Design and Performance Of The Fast Ferrite Tuning Systemmentioning
confidence: 99%
“…Stub tuning networks have been used to reduce power reflected from the plasma on many fusion experiments in the ion cyclotron range of frequencies (<∼ 100 MHz) [1,2] but have not yet been deployed at higher frequencies. A double stub matching network with electronically controlled tuning stubs is under development for the lower hybrid current drive (LHCD) system on Alcator C-Mod [3,4].…”
Section: Introductionmentioning
confidence: 99%